2022
DOI: 10.1155/2022/5910575
|View full text |Cite
|
Sign up to set email alerts
|

CCNA2 as an Immunological Biomarker Encompassing Tumor Microenvironment and Therapeutic Response in Multiple Cancer Types

Abstract: Background. Cancer is a major threat to human health worldwide. Although recent innovations and advances in early detection and effective therapies such as targeted drugs and immune checkpoint inhibitors have saved more lives of cancer patients and improved their quality of life, our knowledge about cancer remains largely unknown. CCNA2 belongs to the cell cyclin family and has been demonstrated to be a tumorigenic gene in multiple solid tumor types. The aim of the present study was to make a comprehensive ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 58 publications
0
23
0
Order By: Relevance
“…Even the emergence of checkpoint inhibition has alleviated this condition, and the combination of immune blockade and targeted therapy has been the standard of management for advanced ccRCC patients [39]. The major challenges facing clinical practitioners were that only a substantial proportion of patients could benefit from checkpoint blockade and the extremely horrible adverse reactions of such therapies [40,41]. Thus, it is urgent to identify new therapeutic targets or adjuvants to aid immune therapy for ccRCC.…”
Section: Discussionmentioning
confidence: 99%
“…Even the emergence of checkpoint inhibition has alleviated this condition, and the combination of immune blockade and targeted therapy has been the standard of management for advanced ccRCC patients [39]. The major challenges facing clinical practitioners were that only a substantial proportion of patients could benefit from checkpoint blockade and the extremely horrible adverse reactions of such therapies [40,41]. Thus, it is urgent to identify new therapeutic targets or adjuvants to aid immune therapy for ccRCC.…”
Section: Discussionmentioning
confidence: 99%
“…With the exception of SKA3, these eight genes have established protein-protein interactions ( Figure 4 ), with protein activities implying that viral load is associated with numerous core functions across the cell cycle process. Specifically, these core functions include initiation of DNA replication [via MCM4-led increased DNA helicase unwinding ( Bochman and Schwacha, 2009 ), and loading of DNA polymerase alpha onto chromatin through CDC45 and possibly GINS complex activity ( Bochman and Schwacha, 2009 )]; and positive regulation of progression through G1, S and G2 phases through CCNA2 ( Jiang et al., 2022 ). Notably, CCNA2 has been associated with aberrant cell cycle progression in several types of cancer, and has been posited as a potential therapeutic target that could be inhibited to repress cell proliferation ( Ma, 2019 ; Yang et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we revealed some key proteins that may be closely related to CENPM by correlation analysis and PPI network construction, including: CCNA2, CCNB2, CDC20, AURKB, ASPM, BUB1 and TOP2A. Interestingly, these molecules have been shown to be associated with the malignant phenotype and poor prognosis of ccRCC in past studies [27][28][29][30]. Not only does this evidence provide a potential regulatory network, it also seems to indirectly validate the malignant function of CENPM in ccRCC.…”
Section: Discussionmentioning
confidence: 98%